Rehabilitating Psychological Well-being in the Postpartum Phase: The Impact of Yoga Therapy and Overcoming Challenges - Vinu W; Dilshith A. Kabeer (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose. The study aimed to promote, foster, and cultivate psychological well-being among women during their postpartum phase and devise yoga-based interventions that enhance the psychological well-being of postpartum women.